2016
DOI: 10.1016/j.jml.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between comprehension and production processes in code-switched language

Abstract: We employ code-switching (the alternation of two languages in bilingual communication) to test the hypothesis, derived from experience-based models of processing (e.g., Boland, Tanenhaus, Carlson, & Garnsey, 1989; Gennari & MacDonald, 2009), that bilinguals are sensitive to the combinatorial distributional patterns derived from production and that they use this information to guide processing during the comprehension of code-switched sentences. An analysis of spontaneous bilingual speech confirmed the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 75 publications
(97 reference statements)
4
62
0
1
Order By: Relevance
“…During bilingual language production, cost-free language switches have been observed when bilinguals memorized and then repeatedly produced mixed-language sentences with long (1500 ms) and obligatory intervals between every word (Declerck & Philipp, 2015), with long intervals between successive stimuli (3200 ms) affording ample preparation time (Mosca & Clahsen, 2015), when the task that showed cost-free switches was only ever performed in one language (Finkbeiner et al, 2006), or when experimental demands led switching to become the default behavior (Gollan & Ferreira, 2009, Experiment 2). During language comprehension, bilinguals have exhibited cost-free switching when reading written words either silently or aloud (Gullifer, Kroll, & Dussias, 2013; Guzzardo Tamargo, 2012; Ibáñez, Macizo, & Bajo, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…During bilingual language production, cost-free language switches have been observed when bilinguals memorized and then repeatedly produced mixed-language sentences with long (1500 ms) and obligatory intervals between every word (Declerck & Philipp, 2015), with long intervals between successive stimuli (3200 ms) affording ample preparation time (Mosca & Clahsen, 2015), when the task that showed cost-free switches was only ever performed in one language (Finkbeiner et al, 2006), or when experimental demands led switching to become the default behavior (Gollan & Ferreira, 2009, Experiment 2). During language comprehension, bilinguals have exhibited cost-free switching when reading written words either silently or aloud (Gullifer, Kroll, & Dussias, 2013; Guzzardo Tamargo, 2012; Ibáñez, Macizo, & Bajo, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…When a language switch occurs immediately after one of these tightly language-anchored elements, the longer delay in acknowledgment of a language switch can be taken as a measure of surprisal at the rupture of bonds implicitly regarded as unbreakable, even though a single morphosyntactic system is involved. The acceptability of code-switching combinations has been linked to frequency-based statistical learning (e.g., Guzzardo Tamargo 2012;Guzzardo Tamargo et al 2016;Valdés Kroff et al 2018), and the results of Experiment 1 as well as the previously-reported data on Quichua-Media Lengua bilingualism have shown that both subject pronouns and interrogatives are closely bound to a single language. Thus, upon hearing a subject pronoun or an interrogative, listeners implicitly anticipate a continuation in the same language and evidently take longer to realize that a switch has occurred immediately following the key item.…”
Section: Resultsmentioning
confidence: 95%
“…Broadly speaking, much of the early work on code-switching indicates that, just like in task switching (Monsell 2003) and cued-language switching (Meuter and Allport 1999), integrating code-switches in realtime processing leads to greater switch costs relative to unilingual processing (Altarriba, Kroll, Sholl and Rayner 1996;Litcofsky and Van Hell 2017). Nevertheless, recent available literature has revealed that switch costs may be attenuated under certain social or linguistic contexts (Beatty-Martínez and Dussias 2017; Fricke, Kroll and Dussias 2016;Guzzardo Tamargo, Valdés Kroff and Dussias 2016;Valdés Kroff, Guzzardo Tamargo, and Dussias 2018). One plausible account for the discrepancy between the ubiquity of code-switching in bilingual speech and the cognitive costs of its integration in comprehension is due to its unexpectancy in labbased studies.…”
Section: Introductionmentioning
confidence: 99%